A new method for the estimation of age at death by using electrical impedance: A preliminary study. Issue 6 (November 2015) - Nishida, Atsushi; Kim, Wook-Cheol; Yoshida, Takashi; Oka, Yoshinobu; Yamada, Naotake; Nakase, Masashi; Ikoma, Kazuya; Fujiwara, Hiroyoshi; Ishikawa, Noboru; Ikegaya, Hiroshi; Kubo, Toshikazu
Graphical abstract: Highlights: This is the first report to analyze the impedance value of bones during autopsies. It was thought that impedance value of bones reflected bone mineral density. The tibial impedance value is thought to be the most useful for estimation of age. This method is a quantitative, inexpensive, and portable method of assessment. Combining this method with other methods could contribute to age-at-death estimation. Abstract: Estimation of age at death is an important part of physical and forensic anthropology. The aim of this study was to investigate whether bioelectrical impedance analysis (BIA) of long bones can be used in the field of forensic medicine as a method to estimate age at death. BIA is easy to use and allows repeat measurements to be taken over time, and the equipment is inexpensive and portable. Impedance values ( Z values) in 378 long bones (humeri, radii, femora, tibiae) of 40 male (233 bones) and 26 female (145 bones) autopsy cadavers were measured using two wire electrodes (connected to an alternating current device and a measuring device) inserted into the metaphyses of long bones. Computed tomography of the greater trochanter of the femur was also analyzed to evaluate bone mineral density (BMD). The results showed that Z values could be used to estimate age in males, and with an age cut-off point of 50 years in females. When estimating age at death from femur and tibia in males by using BIA, it is not necessary to consider the length of subjects. And it was thought that Z values reflected BMD. Among the long bones, the tibia is the most suitable and easy to use for Z value measurement. Z value measurement is a useful method for quantitative evaluation of age at death that can be performed quickly with inexpensive, portable equipment.